2012
DOI: 10.2166/wst.2012.885
|View full text |Cite
|
Sign up to set email alerts
|

Pedotransfer functions to determine water conducting macroporosity in South African soils

Abstract: Macropores play an important role in the rapid transport of water, solutes and pollutants through the soil. Transport through these pores (>0.5 mm) is dominated by gravitational forces (i.e. matrix forces have low impact) resulting in flow rates orders of magnitude higher than rates that would be predicted, posing problems for modelling and understanding water and solute transport through soils. This study aimed to quantify the water conducting macroporosity (WCM) in a range of soils in South Africa and to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Pagliai and Vignozzi (2002) reported that water movements in soil depend on the size and type of soil structure and pores. The results are consistent with those reported in many studies, showing positive relations between macropores and Ks (Jarvis 2007;Dexter and Richard, 2009;Van Tol et al 2012). However, soil macropores and voids can increase Ks, which are not completely related to unsaturated hydraulic conductivity K(h) (Libohova et al, 2018).…”
Section: Resultssupporting
confidence: 91%
“…Pagliai and Vignozzi (2002) reported that water movements in soil depend on the size and type of soil structure and pores. The results are consistent with those reported in many studies, showing positive relations between macropores and Ks (Jarvis 2007;Dexter and Richard, 2009;Van Tol et al 2012). However, soil macropores and voids can increase Ks, which are not completely related to unsaturated hydraulic conductivity K(h) (Libohova et al, 2018).…”
Section: Resultssupporting
confidence: 91%
“…Soil characteristics needed by the crop models were described for each field individually using the land-type database (ARC, 2006) and pedo-transfer functions (van Tol et al, 2012). Land type in this case is defined as an area with uniform micro-climate, typical terrain morphology, and characteristic soil-distribution pattern in the landscape.…”
Section: Soil Datamentioning
confidence: 99%
“…Field methods in general are more realistic and accurate than laboratory ones because of the larger volume of soil involved and the continuity in the soil profile versus depth and because the soils are also minimal disturbed (Vachaud and Dane, 2002). Tension or double ring infiltrometers are also commonly adopted in the field to measure infiltration rates (Perroux and White, 1988;Timlin et al, 1994;Kechavarzi et al, 2009;Fodor et al, 2011;van Tol et al, 2012). Some advantages of tension infiltrometers, when compared with double rings, include minimal disturbance of soil surface, short testing time and little water requirements (Ankeny et al, 1991).…”
Section: Introductionmentioning
confidence: 99%